PENGETAHUAN DAN HARAPAN MASYARAKAT TERHADAP PERUBAHAN PERUNTUKAN KAWASAN HUTAN DI KABUPATEN INDRAGIRI HILIR - Kuncoro - Ariawan; Surati Surati (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2017)
Changes in forest area may include changes in forest designation through exchange process and release of forest areas such as for plantation and industry. The changes will have direct impact on the community, especiallythose adjacent to the changed forest areas. The study was conducted to find out knowledge and expectations of forest communities as a result of changing in forest areas in Indragiri Hilir Regency, Riau Province.The datawere collected by using community interview method. Respondents were selected by purposive random sampling. The results showed that community's knowledge to the forest, benefits and consequences of forest destruction is negative, while community's knowledge to the existence oil palm companies is positive. This is because community awareness on the forest is still low. The community generally agree if forest area that become oil palm plantations be released from forest area designation, and they expect increase in their income. This is motivated by the fact that the land that had been cultivated for coconut plantations is no longer productive, due to frequent sea water intrusion. Cooperation with company is expected to help the communities build embankments on lands affected by seawater intrusion so that the land can be reused.